Pricing Asset-backed Securities: A Revised Model - Bradka, Lukas (2008)
This paper deals with asset backed securities and the pricing thereof. First, an overview of debt markets is provided with a particular focus on the recent crisis in the sub prime markets. Second, literature surrounding securitization, asset backed securities and related types of debt is analysed and discussed. A revised pricing model for asset backed securities based on two existing models (Ebrahim, 2000; Ebrahim & Ahmed, 2007) is successively developed and implemented in Maple programming language. This model assumes access to symmetric information and provides optimum pricing for securities backed by a deprecating asset while collateralising the loan with the underlying asset and the income of the borrower. Finally, a sensitivity analysis is performed on the model, the results are analysed and conclusions drawn. Further extensions to the model are suggested.